Identification and genetic manipulation of human and mouse oesophageal stem cells. Issue 7 (20th April 2015) - Jeong, Youngtae; Rhee, Horace; Martin, Shanique; Klass, Daniel; Lin, Yuan; Nguyen, Le Xuan Truong; Feng, Weiguo; Diehn, Maximilian
Abstract : Objective: Human oesophageal stem cell research is hampered by the lack of an optimal assay system to study self-renewal and differentiation. We aimed to identify and characterise human and mouse oesophageal stem/progenitor cells by establishing 3-dimensional organotypic sphere culture systems for both species. Design: Primary oesophageal epithelial cells were freshly isolated and fluorescence-activated cell sorting (FACS)-sorted from human and mouse oesophagus and 3-dimensional organotypic sphere culture systems were developed. The self-renewing potential and differentiation status of novel subpopulations were assessed by sphere-forming ability, cell cycle analysis, immunostaining, qPCR and RNA-Seq. Results: Primary human and mouse oesophageal epithelial cells clonally formed esophagospheres consisting of stratified squamous epithelium. Sphere-forming cells could self-renew and form esophagospheres for over 43 passages in vitro and generated stratified squamous epithelium when transplanted under the kidney capsule of immunodeficient mice. Sphere-forming cells were 10–15-fold enriched among human CD49f hi CD24 low cells and murine CD49f + CD24 low CD71 low cells compared with the most differentiated cells. Genetic elimination of p63 in mouse and human oesophageal cells dramatically decreased esophagosphere formation and basal gene expression while increasing suprabasal gene expression. Conclusions: We developed clonogenic and organotypic culture systems for the quantitative analyses of human and mouse oesophageal stem/progenitor cells and identified novel cell surface marker combinations that enrich for these cells. Using this system, we demonstrate that elimination of p63 inhibits self-renewal of human oesophageal stem/progenitor cells. We anticipate that these esophagosphere culture systems will facilitate studies of oesophageal stem cell biology and may prove useful for ex vivo expansion of human oesophageal stem cells.